PENERAPAN ZAKAT PRODUKTIF DAN PELATIHAN KEWIRAUSAHAAN DALAM PENGEMBANGAN UMKM DI KOTA BANDUNG - Andini Latifah; Popi Herawati; Wafa Abdullah (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung, 2021)
Zakat has the potential to be developed economically. When viewed from its growth, zakat has experienced rapid development, especially in the past decade. However, the growth of zakat is still very far from the actual zakat potential. Judging from the actual data on the collection of national ZIS by the official OPZ, in 2016 the collection of new ZIS reached around Rp 5 trillion, that means the realization of the collection was still quite far from potential. This gap is more or less influenced by several factors, such as: Low awareness of obligatory zakat (muzakki). In addition, the distribution system of zakat which is still limited to meet consumer needs which ultimately makes zakat not work optimally in alleviating economic problems. So that it takes a movement to utilize the zakat funds with a productive zakat system. The author uses the method of literature study and field research to obtain data. The implementation of productive zakat in Bandung City Baznas is carried out by distributing zakat funds to UMKM to increase the economic productivity of mustahik. Not only given venture capital, but also carried out assistance and coaching by the Office of Cooperatives and UMKM Bandung by holding entrepreneurship training that is focused on the Technical Guidance program (BIMTEK) including resource persons and instructors who will provide guidance on product marketing strategies, bookkeeping and so on. and both processes have an influence in the framework of developing small and medium micro businesses (UMKM) in the city of Bandung.Keyword : Productive zakat, Entrepreneurship training, UMKM.